Implementasi Metode Electre Dalam Penentuan Kepala Laboratorium Rumah Sakit - Ariwisanto Sianturi, Fricles; Sitio, Arjon Samuel (MEANS (Media Informasi Analisa dan Sistem), 2023)
The ELECTRE (Elimination Et Choix Traduisant la Realité) method is a multi-criteria decision-making method that can be used to select the best candidate from a number of predetermined alternatives. Application of the ELECTRE method in determining the head of the hospital laboratory. Human love can be done in several steps. Current problems with RS. Human Love includes criteria that are not yet relevant to determine the head of the hospital laboratory. Human love can be determined based on the needs and priorities of the organization. The long-term goal of this study was to improve the keriteria set in hospitals. Kasih Insani runs correctly, the application built can later be used by the Hospital. Thus the expected result will be the determination of the head of the laboratory at the hospital. Human Love is as expected based on the calculation of methods and criteria that have been set, applications built with the implementation of the Electre method can be used at Rs. Kasih Insani. The plan of this research activity is carried out directly to the Hospital in testing the success of the system built.